A Generational War Is Launched with The Birth of Ok Boomer in The Digital Age - Lim, Young Joon; Lemanski, Jennifer (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
This study examined recent virality of â€œOk Boomerâ€ in the United States. The term of Ok Boomer gained overnight momentum in the public sphere as the symbol of a generational war. While previous research has primarily examined racial and gender tensions, this study introduced a new phenomenon of the generational conflict between â€œOk Boomersâ€ and â€œBaby Boomers,â€ in which social media originated the term of Ok Boomer and traditional media diffused it with framed meaning. Diffusion of Innovation theory was used to better understand the path of how â€œOk Boomerâ€ as a catchphrase, hashtag, noun cluster or trend resulted in attracting a massive amount of media and public attention. Relying on Node XL, Google Trends, and Nexus Nexis for data gathering and analyses, this study categorized four themes for a word, or an idea as an innovation to be publicly acknowledged: collaboration of social media and traditional media, public figuresâ€™ involvement for debate; confrontational social issues, and media-framed agenda. In sum, this study argues the term of Ok Boomer symbolizes the advent of a generational war in society in line with the long-standing race and gender wars in the media coverage.